Spillover effects in stock index returns within Chinese oil industry chain - Lei, Likun; Wang, Yu; Wu, Liang; Mao, Yufeng (Frontiers in Physics, 2025)
With the global energy market becoming increasingly tight and the rapid development of Chinese oil industry, the transmission of information and mutual influence among sectors have become increasingly prominent. In light of this, this paper focuses on the three major sectors within Chinese oil industry chain from 2014 to 2024: oil extraction, oil processing, and oil trading. By employing the TVP-VAR-DY and BK models, we analyze the return spillover effects and dynamic correlations among the upstream, midstream, and downstream sectors of the oil industry chain. The results indicate that there are significant return spillover effects among these three sectors, with their price fluctuations not existing independently but rather influencing and being influenced by each other. Specifically, the oil trading sector predominantly acts as a spillover recipient, while the oil processing sector consistently serves as a net spillover transmitter across the three markets. Furthermore, as the frequency of spillovers increases, the spillover index among the three markets gradually decreases. Notably, when confronted with extreme event shocks, the overall total spillover level of the oil industry system significantly amplifies.